Методика розслідування втягнення неповнолітнього у заняття жебрацтвом - Довгань, Андрій Ігорович (Приватний вищий навчальний заклад «Львівський університет бізнесу та права», 2019)
У дисертації викладено теоретичні положення та науково обґрунтовано рекомендації щодо виявлення та розслідування підрозділами Національної поліції України втягнення неповнолітніх у заняття жебрацтвом, передбачених ст. 304 КК України. Досліджено ступінь наукового розроблення зазначеної проблематики, проаналізовано праці науковців у цій сфері, які стали теоретичною основою дослідження. Визначено стан, структуру і динаміку злочинних дій, пов’язаних із втягненням неповнолітніх у заняття жебрацтвом, криміналістичну характеристику цього злочину та основні детермінанти, які впливають на його вчинення, виявлення та розслідування. Проаналізовано джерела отримання фактичних даних щодо ознак готування та вчинення втягнення неповнолітніх у заняття жебрацтвом. Розкрито специфіку діяльності органів досудового розслідування, пов’язану із розслідуванням втягнення неповнолітніх у заняття жебрацтвом. Охарактеризовано тактику проведення окремих процесуальних дій і порядок використання спеціальних знань. Розроблено пропозиції щодо удосконалення нормативно-правового урегулювання діяльності оперативних підрозділів та органів досудового розслідування Національної поліції України з виявлення та розслідування цього виду злочину. В диссертации изложены теоретические положения и научно обоснованные рекомендации к выявлению и расследованию подразделениями Национальной полиции Украины вовлечения несовершеннолетних в занятие попрошайничеством, предусмотренные ст. 304 УК Украины. Исследована степень научной разработки указанной проблематики, проанализированы труды ученых в этой сфере, которые стали теоретической основой исследования. Определено состояние, структуру и динамику преступных действий, связанных с вовлечением несовершеннолетних в занятие попрошайничеством, криминалистическую характеристику этого преступления и основные детерминанты, которые влияют на его совершение, выявление и расследование. Проанализированы источники получения фактических данных относительно признаков приготовления и совершения вовлечения несовершеннолетних в занятие попрошайничеством. Раскрыта специфика деятельности органов досудебного расследования, связанная с расследованием вовлечения несовершеннолетних в занятие попрошайничеством. Охарактеризованы тактика проведения отдельных процессуальных действий и порядок использования специальных знаний. Разработаны предложения по совершенствованию нормативно-правового регулирования деятельности оперативных подразделений и органов досудебного расследования Национальной полиции Украины по выявлению и расследованию этого вида преступления. The thesis outlines the theoretical concepts and scientifically grounded recommendations for the detection and investigation units of the National Police of Ukraine attracting a juvenile in begging under Art. 304 of the Criminal Code of Ukraine. The degree of scientific development of these problems is investigated, the works of scientists in this field, which became the theoretical basis of the research, are analyzed. The status, structure and dynamics of criminal activities involving the attracting a juvenile in begging have been identified. The thesis also defines the forensic characterization of this crime and the main determinants that influence its commission, detection and investigation. The sources of obtaining actual data on the signs of preparation and attracting a juvenile in begging are analyzed. The specifics of the activities of pre-trial investigation bodies related to the investigation of the attracting a juvenile in begging are disclosed. The tactics of carrying out individual procedural actions and the procedure for the use of specialized knowledge are characterized. Proposals to improve the regulatory framework for the activity of operational units and bodies of pre-trial investigation of the National Police of Ukraine for the detection and investigation of this type of crime have been developed. On the basis of determining the needs of practical activity of units of the National Police of Ukraine the author defines the concept of «forensic characteristics of attracting a juvenile in begging» and substantiates the set of elements of forensic characteristics of this type of criminal offense. After analyzing the scientific literature, statistics and data obtained during the questionnaire survey of practitioners of the National Police of Ukraine, groups of persons who attract a juvenile in begging were identified. Traditional forensic footprints, which indicate the commission of this type of criminal offense and how they can be detected during the scene inspection, are characterized. Based on the survey, the factors that most influence the investigative situation in the investigation of the involvement of juvenile in begging are identified. Based on the analysis of the judicial investigative practice, the classification of typical investigative situations of the initial and subsequent stages of the investigation into the attracting a juvenile in begging is given. Tactical features of the main investigative (search) actions that are conducted during the investigation of the attracting a juvenile in begging are highlighted and outlined. The difficulties that arise in the interrogation of a juvenile attracted in begging and ways of avoiding them are described. The circumstances to be found in the interrogation of a juvenile and the suspect in the investigation into the attracting of a juvenile in begging are identified.
Методика расследования вовлечения несовершеннолетнего в занятие попрошайничеством
Methods of investigation attracting a juvenile in begging
Keywords: втягнення у заняття жебрацтвом; досудове розслідування; збирання доказів; злочин; криміналістична характеристика; неповнолітній; вовлечение в занятие попрошайничеством; досудебное расследование; сбор доказательств; преступление; криминалистическая характеристика; несовершеннолетний; attracting in begging; pre-trial investigation; gathering of evidence; crime; forensic characteristics; juvenile; 343.345-053.6:343.226]:343.1(043.5)